Soil The Skin of the Planet Earth - Kutílek, Miroslav; Nielsen, Donald R. (Springer Netherlands : Imprint: Springer, 2015)
The main focus of this monograph is to explain the important role of soil and the environment to a broad audience. Soil is one of the five essential factors crucial for human life. On the one hand the authors describe a responsible approach and use of soil, established on a basic knowledge of the nature of soil and the countless ongoing processes within soil. On the other hand they explain the precarious link between soil and regional environment, which is indispensable for plant and animal communities.  In addition to these topics its chapters describe the unique roles of soil texture, soil structure and soil pore systems in hydrologic cycles, plant nutrition and conditions affecting the preservation or eventual extinction of soil. This book concludes with the principles of soil protection and revitalization. General readers with an interest in biology, chemistry, physics or geology will find this book highly informative.